Effectiveness of Big Five Traits on Classroom Management in Teaching English Language in Palestinian Schools - Bsharat, Tahani R. K.; Behak, Fariza Puteh; Selamat, Suzanah Binti; Barahmeh, Mosaddaq Y.; Dweikat, Khaled Abdul-Jaleel; Zyoud, Munther; Salama, Imad. A. A.; Issa, Eman I. (Advances in Social Sciences Research Journal, 2023)
Teachers have a critical influence on the success or failure of any educational institution. The effectiveness of teachers is thought to be the most important component in influencing pupils’ academic progress. This paper is intended to find out the effectiveness of Big Five Traits toward classroom management in English language teaching in Palestinian schools. This study used a fully quantitative method with a survey as its data collection method where the participants were 35 elementary school teachers. Out of the total number of the participants, 45.7% were females, 34.3% were aged between 23-30 or 31-40 years old, 85.7% had Bachelor’s degrees, and 37.1% reported having over 10 years of teaching experience. The result of this study showed that there was a strong positive correlation between the teachers’ big five personality traits and their effective classroom management practices.